THE STUDY OF CONVERSATIONAL UTTERANCES IN A STAR IS BORN MOVIE - Febri Rhamadani, Siti Natasya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2021)
This thesis studies conversational implicature in A Star is Born Movie. A Star Is Born is a 2018 American romantic musical drama film starred by Cooper, Lady Gaga, Dave Chappelle, Andrew Dice Clay, and Sam Elliott. It tells the story about a hard-drinking musician (Cooper) who discovers and falls in love with a young singer (Gaga). The research focuses on the conversations between characters in the movie. The objectives of the study are 1) to identify the conversational implicatures utterances on A Star Is Born movie, and 2) to analyze the conversational implicatures which have additional meaning. This research is qualitative research. To analyze the data, the study uses Grice’s theory of conversational implicature; Generalized conversational implicature, and particularized conversational implicature. The result of the study shows that: First, there are 375 data containing conversational implicature. Those conversational implicature are divided into two, generalized implicature and particularized implicature. From 375 conversational implicature, there are 220 utterances belong to generalized implicature and 155 utterances belong to particularized implicature. Second, all conversational implicature have additional meaning. It means, there are 375 data of conversational implicature have additional meaning.